Application of the Finite Element Method Using Cohesive Elements to Model the Effect of Temperature, Rock Mechanical Properties, Fluid Injection Rate, and Fluid Properties on the Development of Hydraulic Fracture Height. (25th May 2022) - Pham, Son Tung; Nguyen, Ba Ngoc Anh
Abstract : Although hydraulic fracturing has been practiced all over the world, the research on how the fracture height develops in time and space still leaves some missing gaps. The fracture height has been considered in most cases equal to the pay zone thickness, and the influence of temperature in this process has been omitted. Therefore, the aim of this paper is to study the effect of temperature, rock mechanical properties, and fluid injection rate on the development of the fracture geometry, especially on the fracture height. A multiphysics model was implemented using cohesive elements in a finite element model generated with equations in fracture mechanics. Once the model was calibrated with experimental data, it was used to conduct sensitivity studies to reveal the influence of main contributed factors such as the properties of rocks and fluids used in hydraulic fracturing, the injection rate of fracturing liquid, and especially the influence of temperature because this last aspect was omitted in literature review from previous studies. The results indicated that the fracture height depended strongly on the rock properties, not only the rock in the pay zone but also the ones in the adjacent layers. Besides, the influence of the fluid injection rate on the fracturing height is so great that it overwhelms the influence of temperature and mechanical parameters. Moreover, the impact of the leak-off coefficient is much less remarkable than that of the fluid viscosity, which demonstrates why in reality it is important to control the viscosity to achieve desirable results. This study can be applied in real life problems to predict fracture's geometry generated in well stimulations.